AN INVESTIGATION INTO ATHLETES' EATING ATTITUDES - Şam, Cemi̇l Tuğrulhan; Budak, Davut; Gürbüz, Ali̇; Gökkuş, Zeynep; Yilmaz, Hasan Hüseyin; Kaldirimci, Murat (Zenodo, 2017)
Abstract This aim of this study is to investigate eating attitudes among athletes who do active exercise. The study was conducted with 161 individuals 19±1.86 years of age who are students at Atatürk University Sport Sciences Faculty in Erzurum. Two different scales were applied to individuals participating in the study. The first applied scale is the ID form which is tdesigned o obtain personal information. The second scale applied is the Eating Attitude Test (EAT) which is to determine eating disorders and eating attitudes. The analysis of acquired datas is done using SPSS (version 22) and Significance for statistical datas was selected being p<0.05. As a result of study, individuals participating in the study’s EAT levels were found to be fairly high. According to these results, it can be said that Athletes have eating disorders. Nevertheless, there were no significant differences in EAT levels according to state of family income, abode,smoking, or alcohol use.
Keywords: attitude; public health; physical activity; athlete; sport; eating